The effects of the fractions of Piper sarmentosum leaves on inhibition of adipogenesis of 3T3 L1 preadipocytes - Fairus Ahmad,; Ima Nirwana Soelaiman,; Khairana Husain,; Farihah Hj Suhaimi,; Chua, Kien Hui; Norzana Abd Ghafar, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Piper sarmentosum Roxb. was reported to have anti-obesity, hypoglycaemic and anti-oxidant properties. The aim of this study was to identify the fractions of P. sarmentosum leaf extract in inhibiting adipogenesis of 3T3L1 preadipocytes. The crude extract of the P. sarmentosum leaves was fractionated to produce hexane, dichloromethane, methanol, and aqueous fractions. Various dilutions of the fractions; hexane (0.1 - 1 μg/mL), dichloromethane (9.76 - 97.6 μg/mL), methanol (3.6 - 36 mg/mL), and aqueous (1 - 10 mg/mL), were treated onto the 3T3L1 preadipocytes from 3rd to 15th day of culture. The crude extract (1 - 10 mg/mL) and glycyrrhizic acid (GCA) (0.24 - 2.4 mg/mL) were used as positive controls. The viability of the adipocytes was measured by MTT assay at the 15th day of culture. The content of each fraction was quantified with reference standards of naringin, naringenin, pellitorine, sarmentosine and β-sitosterol by using HPLC. The results showed that 49.1% of the crude extract contained aqueous fraction, 0.12% in hexane fraction, 9.7% in dichloromethane fraction and 36% in methanol fraction. The aqueous fraction and crude extract at the dose of 7 mg/mL and GCA at the dose of 1.92 mg/mL showed potent inhibitory effects on the adipogenesis. However, none of the reference standards were identified from the fractions using HPLC analysis. In conclusion, the aqueous fraction was the main fraction in the crude extract of the P. sarmentosum and contributed a significant role in inhibiting adipogenesis of the 3T3L1 preadipocytes.